Maternal transfer of anthropogenic radionuclides to eggs in a small shark. (September 2015) - Jeffree, Ross A.; Oberhansli, Francois; Teyssie, Jean-Louis; Fowler, Scott W.
Abstract: Maternal transfer of radionuclides to progeny is one of the least known sources of contamination in marine biota and more information is needed to assess its radiological significance. A radiotracer study on spotted dogfish, Scyliorhinus canicula, evaluated the hypothesis that four anthropogenic radionuclides (Cobalt-60, Zinc-65, Americium-241 and Cesium-134) could be maternally transferred to eggs and each of their major components during maternal ingestion of radiolabelled food. The linear regressions between cumulative radioactivity that had been maternally ingested and the level in subsequently laid eggs were used to derive maternal-to-egg transfer factors (mTFs). These maternal transfers varied over an order of magnitude and were ranked 134 Cs >  65 Zn >  60 Co >  241 Am. This ranking was the same as their relative assimilation efficiencies in radiolabelled food consumed by adults. Among these four radionuclides the potential radiological exposure of embryos is accentuated for 65 Zn and 134 Cs due to their predominant transfer to egg yolk where they are available for subsequent absorption by the embryo as it develops prior to hatching from the egg capsule. Thus, for cartilaginous fish like shark, the potential radioecological consequences of a pulsed release of these radionuclides into the marine environment may extend beyond the temporal duration of the release. Highlights: Dogfish maternally transfer anthropogenic radionuclides to eggs. Transfers are ranked 134 Cs >  65 Zn >  60 Co >  241 Am. Both 65 Zn and 60 Co are mainly deposited in yolk.